Acceptance of Electric Vehicle based on Pricing and Charging Station / H. M. S. Firdaus ...[et al.] - S. Firdaus, H. M.; Halyani, M. Y.; Osman, M. H.; Maidin, N.A.; Ahmad, M. N.; A. Rahman, M. H.; Damanhuri, A. A.; Wahid, M. K. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
In the middle of 19th century, electric vehicle (EV) has taken place as favourite energy resources for car driving. EV does not have vibration, smell or noise in their operation that gives advantage compared to internal combustion vehicle. However, integration of electrical-based engine technology required extra cost and installation of public charging points. This study focus on finding out the acceptance of EV among Malaysian based on the pricing and charging station. This is due to the environmental problems caused by vehicles emissions that leads to greenhouse effect. Besides, the price of EV is more expensive than internal combustion vehicle and there are limited charging station provided. A survey was conducted in Gombak and Melaka Tengah by using simple random sampling. Sample size of 384 respondents were selected form each district out of 682,226 (Gombak) and 503,127(Melaka Tengah) population. About 46.74% of the respondents agreed to buy EV if the price is less than MYR 50,000 and 87.37% of the respondents agreed to purchase EV if access to a charging station is provided at commercial parking lot or garage. Unwillingness to pay for more than MYR 50,000 means that the community has a low financial ability instead of their interest to own an electric vehicle if public charging station are provided.